1998
DOI: 10.1103/physrevlett.81.192
|View full text |Cite
|
Sign up to set email alerts
|

k-Dependent Electronic Structure, a Large “Ghost” Fermi Surface, and a Pseudogap in a Layered Magnetoresistive Oxide

Abstract: The k-dependent electronic structure of the low temperature ferromagnetic state of La 1.2 Sr 1.8 Mn 2 O 7 was measured using angle-resolved photoemission spectroscopy and calculated using the local spin density approximation (LSDA). The measured near-Fermi energy states display E vs k and symmetry relationships which agree relatively well with the LSDA prediction through much of the Brillouin zone, and the locus of lowest energy excitations matches the predicted large Fermi surface quite well. However, the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
154
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 25 publications
30
154
1
4
Order By: Relevance
“…The existence of this pseudogap feature was remarked theoretically in [24]. Photoemission experiments have also unveiled a similar behavior in bilayer manganites [25]. It is expected that pseudogaps would appear in the density of states in the regimes of inhomogeneities, as a natural consequence of the competition between a metal (flat DOS) and an insulator (gapped DOS).…”
Section: Electronic Phase Separation In Manganitesmentioning
confidence: 72%
“…The existence of this pseudogap feature was remarked theoretically in [24]. Photoemission experiments have also unveiled a similar behavior in bilayer manganites [25]. It is expected that pseudogaps would appear in the density of states in the regimes of inhomogeneities, as a natural consequence of the competition between a metal (flat DOS) and an insulator (gapped DOS).…”
Section: Electronic Phase Separation In Manganitesmentioning
confidence: 72%
“…Note that this does not correspond to the usual atomic, anti-adiabatic limit [35], where it is assumed from the beginning that D → 0 is the smallest energy scale in the problem, resulting in dispersionless high energy features. The present theory is valid in the opposite limit, D ≫ ω 0 , which is more often realized in solids [36,37,38]. Due to the large transfer integrals between molecular units, the discrete shakeoff spectrum characteristic of isolated molecules is converted here into a continuous gaussian spectral density [16], and a sizeable high-energy dispersion is recovered.…”
Section: B Strong Coupling Limitmentioning
confidence: 80%
“…This last observation is puzzling given the general expectation of strong interactions in the manganites. Moreover, the value for the inplane conductivity calculated with the ARPES parameters is nearly one order of magnitude higher than that measured by transport [9][10][11] .…”
mentioning
confidence: 96%
“…For a single polaron the spectral function consists of a low-energy 'zero-phonon' quasiparticle peak representing the centre of mass of the quantum motion of the polaron, and a high-energy incoherent resonance. It was recently demonstrated that in general the peak position of the incoherent resonance has to track closely the bare dispersion 9,[15][16][17] . This reflects the motions of the undressed electron confined in the polaron cloud, and a similar picture has been suggested for underdoped copper oxides 15 .…”
mentioning
confidence: 99%